Islam, Science, and Civilization: Prospect and Challenge for Humanity - JIS, Presenter of (Joint International Seminar)
This Joint International Seminar Proceeding is intended and aimed at reexploring the values of modern science that have been lost. Considering the current crisis of modern civilization, constructing principles of modern science which are based on divinity and humanity is a must as well as formulating spiritualized framework of modern science. Therefore, this proceeding identifies not only the agenda of modern science and technology which are based on divinity principles but also extensive strategic networks for Islamic science development that are useful for civilization development. Through this proceeding, UIN Walisongo in cooperation with UTM Malaysia performed a civilizational duty to discuss some important topics such as the humanization of science and technology, the unity of sciences for humanity, Muslim contribution to Asian civilization, and science and technology future agenda. The target of this proceeding is to compile strategic formula in the face of prospects and challenges for the efforts to fulfill the divinity values to modern science.